Flood Detection in Complex Surface Mining Areas Using Satellite Data for Sustainable Management - Konstantinos Karalidis; Georgios Louloudis; Christos Roumpos; Eleni Mertiri; Francis Pavloudakis (Materials Proceedings)
In the context of the lignite phase-out plan in Greece, the aim of the Public Power Corporation (PPC) is sustainable mine closure and land reclamation and, at the same time, the enhancement of safe mining and post-mining activities. The main objective of this study is to provide a methodology to identify the areas in complex surface mining landscapes that are more vulnerable to flooding using remotely sensed satellite data. This is an integral part of the strategic planning of the new land uses and the design of new and improved water management strategies. In this research, the change detection method is applied using Synthetic Aperture Radar (SAR), and flood-prone zones are delineated.